Media panel 1995/96 - V63-33y - Rosengren, Karl Erik; Windahl, Sven; Johnsson-Smaragdi, Ulla; Höjerback, Ingrid; Sonesson, Inga (Linnaeus University, 1999)
The Media Panel Program (MPP) is located at the University of Lund in Sweden. It is a long-term research program focused on basic aspects of the mass media use by Swedish children, adolescents and young adults, as well as on the causes, consequences and effects of that media use. The program was founded by professors Karl Erik Rosengren and Sven Windahl in 1975, after a series of preliminary studies. Since 1995, the program has been directed by professor Ulla Johnsson-Smaragdi. Data have been collected in Malmö (an industrial city in southern Sweden; some 230 000 inhabitants) and Växjö (a college and cathedral town in southern Sweden; some 60 000 inhabitants). The techniques used for data collection include mail and classroom questionnaires, personal interviews, essays written by school children at school, archival data, focused interviews, and long, in-depth conversations with a small number of type-representative individuals. For children and adolescents in grade 3-9 (age 10 to 16) in the compulsory school system, class room questionnaires were used. For older adolescents and young adults, as well as for parents, mail questionnaires were used. School grades and similar data were culled from school archives. During a long period of continuous research the MPP group has produced a data bank in which a large mass of data related to individual media use, its causes, effects and consequences are stored, covering a number of cohorts and panels of children and adolescents passing through the school system and into work or continued studies during their early adulthood. In all, the bank contains data about: some 5 000 children, adolescents and young adults; their family background, activities and relations; their relations to peers and their school experiences (including school grades etc.); their media use, life styles, present occupation and activities, as well as their plans for the future. Relevant data from their parents have also been collected on several occasions.

Year of data collection 1995/1996. Cohort: Växjö, born in 1963, 33 years old.

En särskilt viktig grupp i massmediesammanhang är barn och ungdom. Man antar att de intryck barnen redan från tidig ålder mottar från massmedierna starkt påverkar hur de uppfattar sig själva, det svenska samhället och vår internationella omgivning. Forskningsprogrammet Mediapanel undersökte dessa frågor. Programmet var uppbyggt kring en så kallad panelstudie, där skolungdomar i Växjö och förskolebarn och skolungdomar i Malmö vid flera tillfällen intervjuades om sina massmedievanor.
Mediapanelens databas började byggas upp i mitten av 1970-talet och sträcker sig över närmare 25 år. Totalt innehåller den data om drygt 5 000 barns och ungdomars familjebakgrund och uppväxtmiljö, aktiviteter, medieanvändning och attityder till medierna.

Mediapanel-programmets design bygger på en kombination av longitudinella studier och tvärsnittsstudier viket gör det möjligt att jämföra jämnåriga kohorter av barn och ungdomar från olika tidsperioder, t ex ungdomar på 70-talet med ungdomar i samma ålder på 80- respektive 90-talet. Det är även möjligt att longitudinellt följa samma barn från förskole- och lågstadieåldern, genom skolåldern och ungdomstiden, upp till vuxen ålder.

Frågorna täcker ett brett spektrum och behandlar t ex hur barn och ungdomar identifierar sig med individer på TV-skärmen, vad de tar del av, hur beroende de upplever sig vara av t ex TV, men också vilka alternativa aktiviteter de deltar i, hur mycket de umgås med familj och kamrater. Även frågor om hur de ser på världen i stort, liksom om deras uppfattning om Sverige och sin egen framtid.

Syfte:

Försöka förklara hur medievanor uppstår, hur de förändras med barnens ålder, vilka faktorer hos barnen själva och i barnens omgivning som hänger samman med en viss medieanvändning, samt vilka konsekvenser detta kan få.

Datainsamlingsår 1995/1996. Kohort: Växjö, födda 1969, 33-åringar.
Mediapanel 1995/96 - V63-33y
Keywords: leisure time; fritid; listening to music; musiklyssnande; television viewing; tv-tittande; schools; skolor; schoolchildren; skolbarn; social activities (leisure); sociala aktiviteter (fritid); radio listening; radiolyssnande; Media; Media; Information society; Informationssamhället; Youth; Ungdomar; Children; Barn; Social behaviour and attitudes; Socialt beteende och attityder; Cultural activities and participation; Kulturaktiviteter och deltagande; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Sociology; Sociologi; Media and Communication Studies; Medie- och kommunikationsvetenskap